IQGAP1: cross-disease target via receptor-pathway networks - Zhu, Shaopeng; Zou, Yunpeng; Guo, Jie; Ma, Wenqi; Lu, Laitong; Liu, Ronghan; Kang, Jianning; Zhao, Kai; Zhong, Jiangbo (Frontiers in Oncology, 2025)
IQGAP1, a versatile scaffolding protein, critically regulates cytoskeletal organization, cell motility, proliferation, and signaling cascades. Beyond coordinating these cellular functions, it is increasingly recognized as a key driver in malignancies, immune dysfunction, metabolic dysregulation, and cardiovascular pathologies. By binding receptor tyrosine kinases, small GTPases, and downstream effectors, IQGAP1 modulates oncogenesis, immune evasion, and metabolic imbalance, while contributing to chemoresistance. This review synthesizes advances in IQGAP1’s structural domains, disease-specific signaling networks, and therapeutic targeting strategies, emphasizing its translational potential in developing precision therapies for cancer, metabolic syndromes, and immune disorders.